Authentication of pineapple (Ananas comosus [L.] Merr.) fruit maturity stages by quantitative analysis of γ- and δ-lactones using headspace solid-phase microextraction and chirospecific gas chromatography–selected ion monitoring mass spectrometry (HS-SPME–GC–SIM-MS). (1st February 2015) - Steingass, Christof B.; Langen, Johannes; Carle, Reinhold; Schmarr, Hans-Georg
Highlights: Chirospecific analysis of lactones in pineapples of different ripening stages. HS-SPME–GC–SIM-MS and stable isotope dilution assay (SIDA) based quantification. Air-freighted fruits characterised by γ-hexalactone (γ-C6) of high enantiomeric purity. Increased ( S )-γ-C6 genesis during post-harvest ripening of sea-freighted pineapples. Authentication of pineapple fruits according to their post-harvest procedures. Abstract: Headspace solid phase microextraction and chirospecific gas chromatography–mass spectrometry in selected ion monitoring mode (HS-SPME–GC–SIM-MS) allowed quantitative determination of δ-lactones (δ-C8, δ-C10) and γ-lactones (γ-C6, γ-C8, γ-C10). A stable isotope dilution assay (SIDA) with d7 -γ-decalactone as internal standard was used for quantitative analysis of pineapple lactones that was performed at three progressing post-harvest stages of fully ripe air-freighted and green-ripe sea-freighted fruits, covering the relevant shelf-life of the fruits. Fresh pineapples harvested at full maturity were characterised by γ-C6 of high enantiomeric purity remaining stable during the whole post-harvest period. In contrast, the enantiomeric purity of γ-C6 significantly decreased during post-harvest storage of sea-freighted pineapples. The biogenetical background and the potential of chirospecific analysis of lactones for authentication and quality evaluation of fresh pineapple fruits are discussed.